3
.Calcule as raízes da equação 6x² - 3x = 5x² + 10


Resposta :

Resposta:

.   S  =  { - 2,  5 }

Explicação passo-a-passo:

.

.      Equação de segundo grau

.

.           6x²  -  3x  =  5x²  +  10

.           6x²  -  5x²  -  3x  -  10  =  0

.           x²  -  3x  -  10  =  0

.

a = 1,     b = - 3,      c = - 10

.

Δ  =  b²  -  4 . a . c

.    =  (- 3)²  -  4 . 1 . (- 10)

.    =  9  +  40

.    =  49

.

x  =  (- b  ±  √Δ  ) / 2.a

.   =  (- (-3)  ±  √49) / 2 . 1

.   =  (+ 3  ±  7) / 2

.

x'  =  (+ 3  +  7) / 2  =  10 / 2  =  5

x"  =  (+3   -  7) / 2  =  - 4 / 2  =  - 2

.

(Espero ter colaborado)

6x² - 3x = 5x² + 10

6x² - 3x - 5x² - 10 = 0

x² - 3x - 10 = 0

∆ = (-3)² - 4.1.(-10)

∆ = 9 + 40

∆ = 49

[tex]x = \frac{ - ( - 3) + - \sqrt{49} }{2 \times 1} [/tex]

[tex]x = \frac{3 + - 7}{2} [/tex]

[tex] x_{1} = \frac{3 - 7}{2} [/tex]

[tex]x_{2} = \frac{3 + 7}{2} [/tex]

[tex] x_{1} = - 2 \\ x_{2} = 5[/tex]